English use anxiety, motivation, self-efficacy, and their predictive effects on Chinese top university students’ English achievements - Wu, Xia; Yang, Huameng; Liu, Junxia; Liu, Ziyu (Frontiers in Psychology, 2022)
The present study examined English use anxiety, motivation, self-efficacy, use of English, and their predictive effects on top university students’ English achievements. Two hundred and twenty-three students of the Top-Notch Students of Basic Disciplines Training Program in a top Chinese university answered a battery of questionnaires, which consisted of the 8-item English Use Anxiety Questionnaire, the 5-item Motivational Self-Talk Questionnaire, the 3-item Self-Efficacy Questionnaire, the 19-item Language Learning Orientations Questionnaire, and a Background Information Questionnaire. Analyses of the data revealed the following major findings: (1) the participants had a low level of extrinsic motivation-introjected regulation, a low-to-medium level of English use anxiety, extrinsic motivation-external regulation, intrinsic motivation-knowledge, and a medium-to-high level of motivational self-talk, self-efficacy, extrinsic motivation-identified regulation, intrinsic motivation-accomplishment, and intrinsic motivation-stimulation, (2) use of English anxiety (UAE) and language learning orientation were generally significantly negatively correlated with each other, and significantly correlated with other measured variables, (3) UAE and intrinsic motivation-knowledge significantly predicted the participants English achievements, measured both by standardized test scores and self-rated overall English proficiency, and (4) use of English and self-efficacy mediated the effects of English use anxiety and language learning orientations on the participants’ English achievements. These findings further pinpoint the importance of anxiety and motivation in second/foreign language learning.